El «Derecho a la seguridad», en la base del desarrollo - Huesca González, Ana (Miscelánea Comillas, 2009)
In a world in constant transformation, the safety is a permanent needin the human being. Not even the most advanced western societies have obtained for his citizens the certainty of this safety in his lives. The safety concept is asocial construction that, therefore, changes in the time and in the space, changes in his content but what does not change is his importance in the life of the persons. With regard to the Human rights it is reason and consequence. As reason,it explains that other rights could not be guaranteed if there is not guaranteed the safety of the citizens of a state. As consequence, it is necessary to beconscious that the breach of the rest of the rights generates insecurity.